A modified kaolinite reinforced flame retardant waste resin composite material and preparation method thereof

By adding modified kaolinite CC-BM@KH-NH2-Kaol to the waste resin, the problems of flammability and insufficient mechanical properties of waste resin materials are solved, and the flame retardant and mechanical properties of waste resin composite materials are achieved. Improved and expanded its application scope.

CN116178843BActive Publication Date: 2025-02-18HUNAN ZHONGCHU NEW MATERIAL TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310221186.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-02-18
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

Existing waste resin materials are flammable and have insufficient mechanical properties, making them difficult to widely use in the industrial field.

Method used

Modified kaolinite CC-BM@KH-NH2-Kaol was prepared by chemically reacting with end amino coupling agent with kaolinite and organic flame retardant, and melt blended with waste resin to form enhanced flame retardant. Waste resin composite material.

Benefits of technology

Modified kaolinite significantly improves flame retardant and mechanical properties in waste resin composite materials, making it have good comprehensive performance under low addition conditions, and is suitable for a wider range of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116178843B_ABST
    Figure CN116178843B_ABST
Patent Text Reader

Abstract

The invention discloses a modified kaolinite reinforced flame retardant waste resin composite material and a preparation method thereof, the preparation method comprising the following steps: step 1: adding cyanuric chloride and a bio-based material to a solvent, stirring and reacting at high temperature to prepare an intermediate compound; the bio-based material is a compound containing both hydroxyl and aldehyde functional groups; step 2: adding a coupling agent containing an amino group to water, fully hydrolyzing, adding dried kaolinite thereto, stirring and reacting at high temperature to prepare kaolinite modified by a coupling agent containing an amino group; step 3: adding the intermediate compound and the kaolinite modified by a coupling agent containing an amino group to a container of deionized water, reacting under stirring conditions to prepare modified kaolinite; step 4: melt blending the dried modified kaolinite and waste resin to prepare a modified kaolinite reinforced flame retardant waste resin composite material. The invention improves the flame retardant and mechanical properties of the waste resin composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste resin modification, and in particular to a modified kaolinite reinforced flame-retardant waste resin composite material and a preparation method thereof. Background Art

[0002] Resin materials are widely used in industrial fields such as daily necessities, automobiles, home appliances and construction due to their excellent mechanical properties, chemical resistance, acid and alkali resistance, stable product size and easy processing. However, the development of the plastics industry has brought convenience to human life, but it has also led to the generation of a large amount of waste plastic garbage; at the same time, most of this type of waste materials are very easy to burn. In order to expand its application range and improve its flame retardant and mechanical properties, adding modified particles to the resin is one of its main preparation methods.

[0003] Kaolinite is a silicate two-dimensional layered nanomaterial, one of the minerals that is widely distributed in the earth's crust and is widely used by humans. It has been greatly and rapidly utilized and developed in the fields of ceramic industry, paper industry, polymer composite materials, fire-resistant and flame-retardant materials, agriculture and medicine, construction and national defense. However, pure inorganic materials have poor compatibility with organic polymer materials. They can be modified with organic flame retardants to prepare new modified kaolinite, which can be applied to waste resins to prepare kaolinite-reinforced flame-retardant waste resin composites, expanding the application of waste resins and kaolinite to a deeper and broader level.

[0004] It should be noted that the above introduction to the technical background is only for the convenience of providing a clear and complete description of the technical solutions of the present application and for the convenience of understanding by those skilled in the art. It cannot be considered that the above technical solutions are well known to those skilled in the art simply because they are described in the background technology section of the present application. Summary of the invention

[0005] In view of the above-mentioned shortcomings, the present invention provides a modified kaolinite reinforced flame-retardant waste resin composite material and a preparation method thereof. The present invention uses a coupling agent with an amino terminal, which is conducive to the reaction of the coupling agent with Kaol after hydrolysis. At the same time, the amino terminal can also react with the aldehyde group in the organic flame retardant to carry out a Schiff base reaction, and connect Kaol and CC-BM through a chemical bond. Therefore, the modified kaolinite CC-BM@KH-NH2-Kaol has better compatibility and dispersibility with the matrix, giving it better flame retardant properties and mechanical properties in the waste resin composite material.

[0006] In order to achieve the above object, the present invention provides a method for preparing a modified kaolinite reinforced flame retardant waste resin composite material, comprising the following steps:

[0007] Step 1: adding cyanuric chloride and a bio-based material into a solvent, stirring and reacting at a high temperature to prepare an intermediate compound; the bio-based material is a compound containing both hydroxyl and aldehyde functional groups;

[0008] Step 2: adding a coupling agent containing a terminal amino group to water, and after sufficient hydrolysis, adding the dried kaolinite thereto, stirring and reacting at a high temperature to prepare kaolinite modified by a coupling agent containing an amino group;

[0009] Step 3: adding the intermediate compound and kaolinite modified by the amino-containing coupling agent into a container of deionized water, reacting under stirring conditions to prepare modified kaolinite;

[0010] Step 4: melt-blending the dried modified kaolinite and waste resin to prepare a modified kaolinite reinforced flame-retardant waste resin composite material.

[0011] According to one aspect of the present invention, in step 1, the bio-based material comprises any one or more of vanillin, lignin, and tannic acid.

[0012] According to one aspect of the present invention, in step 1, the solvent is any one or more of acetone, 1,4-dioxane, and chloroform.

[0013] According to one aspect of the present invention, in step 1, the stirring reaction at high temperature is carried out at a temperature of 60-120° C. and a time of 3-12 h.

[0014] According to one aspect of the present invention, in step 2, the stirring reaction at high temperature is carried out at a temperature of 80-150° C. and a time of 2-8 h.

[0015] According to one aspect of the present invention, in step 2, the coupling agent containing terminal amino groups is any one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane, aminoethylaminoethylaminopropyltrimethoxysilane, and polyaminoalkyltrialkoxysilane (in isopropanol).

[0016] According to one aspect of the present invention, in step 2, the mass ratio of the dried kaolinite to the coupling agent containing terminal amino groups is 10:1.

[0017] According to one aspect of the present invention, in step 3, the molar ratio of the intermediate compound to the kaolinite modified by the amino-containing coupling agent is 1-1.05.

[0018] According to one aspect of the present invention, in step 4, the mass ratio of the dried modified kaolinite to the waste resin is 1-5:97.

[0019] Based on the same inventive concept, the present invention also provides a modified kaolinite reinforced flame retardant waste resin composite material prepared by any of the above preparation methods.

[0020] Beneficial effects of the present invention:

[0021] The modified kaolinite of the present application not only contains nanoparticles Kaol, but also contains N / Si elements (flame retardant elements), which can enhance the flame retardant properties and mechanical properties of nanomaterials in polymer composites. The present application modifies Kaol by CC-BM and KH-NH2, and melt blends it with waste resin to prepare CC-BM@KH-NH2-Kaol enhanced flame retardant waste resin composite material, which is beneficial in that KH-NH2 can connect Kaol and CC-BM through chemical bonds, and then CC-BM and KH-NH2 can effectively improve the dispersibility of Kaol in the matrix resin, and can prepare waste resin functional composite materials with good comprehensive performance under the condition of low addition amount, so that the composite material has good flame retardant properties and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The infrared spectra of CC, BM and CC-BM described in Example 1 of the present invention are shown;

[0023] Figure 2 The infrared spectra of Kaol and KH-NH2-Kaol described in Example 1 of the present invention are shown in FIG.

[0024] Figure 3 This is the infrared spectra of CC-BM@KH-NH2-Kaol, CC-BM, and KH-NH2-Kaol described in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.

[0026] It should be noted that the kaolinite in the present application is abbreviated as Kaol; the cyanuric chloride in the present application is abbreviated as CC; the bio-based material in the present application is abbreviated as BM; the intermediate compound in the present application is abbreviated as CC-BM; the coupling agent containing terminal amino groups in the present application is abbreviated as KH-NH2; the modified kaolinite in the present application is abbreviated as CC-BM@KH-NH2-Kaol; the kaolinite modified by the coupling agent containing amino groups in the present application is abbreviated as KH-NH2-Kaol.

[0027] The flame retardant test and mechanical property test standards of the modified kaolinite reinforced flame retardant waste resin composite material prepared in this application are as follows:

[0028] Flame retardant test: The standard cone calorimeter of Fire Testing Technology Limited of the United Kingdom was used to evaluate the combustion performance of relevant samples according to ISO5600. The heat intensity of the heating radiator in the test was 50kW / m 2 The size of the sample is 100×100×3mm 3 , record the relevant data of the sample after at least five experiments; the limiting oxygen index (LOI) is carried out in accordance with the standard of ASTM2863 / ISO 4589, and the sample size is 50×6.5×3mm 3 .

[0029] Tensile strength: According to GB / T1040-1998, the tensile strength and elongation at break of waste resin and waste resin composite materials are tested and evaluated using an electronic universal testing machine. The size of the standard dumbbell-shaped tensile specimen is 150×10×4mm 3 , the gauge length is 50 mm, the tensile rate is 50 mm / min, and each test sample is tested at least 5 times to take the average value.

[0030] At present, the development of the plastics industry has brought convenience to human life, but it has also led to the generation of a large amount of waste plastic garbage; at the same time, most of this type of waste materials are extremely flammable.

[0031] In order to expand its application scope and improve its flame retardant and mechanical properties, the present invention provides a method for preparing a modified kaolinite reinforced flame retardant waste resin composite material, comprising the following steps:

[0032] Step 1: adding cyanuric chloride and a bio-based material into a solvent, stirring and reacting at a high temperature to prepare an intermediate compound; the bio-based material is a compound containing both hydroxyl and aldehyde functional groups;

[0033] Step 2: adding a coupling agent containing a terminal amino group to water, and after sufficient hydrolysis, adding the dried kaolinite thereto, stirring and reacting at a high temperature to prepare kaolinite modified by a coupling agent containing an amino group;

[0034] Step 3: adding the intermediate compound and kaolinite modified by the amino-containing coupling agent into a container of deionized water, reacting under stirring conditions to prepare modified kaolinite;

[0035] Step 4: melt-blending the dried modified kaolinite and waste resin to prepare a modified kaolinite reinforced flame-retardant waste resin composite material.

[0036] Preferably, in step 1, the bio-based material comprises any one or more of vanillin, lignin, and tannic acid.

[0037] Preferably, in step 1, the solvent is any one or more of acetone, 1,4-dioxane, and chloroform.

[0038] Preferably, in step 1, the stirring reaction at high temperature is carried out at a temperature of 60-120° C. and a time of 3-12 hours.

[0039] Preferably, in step 2, the stirring reaction at high temperature is carried out at a temperature of 80-150° C. and a time of 2-8 h.

[0040] Preferably, in step 2, the coupling agent containing terminal amino groups is any one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropylmethyldiethoxysilane, anilinomethyltriethoxysilane, anilinomethyltrimethoxysilane, aminoethylaminoethylaminopropyltrimethoxysilane, and polyaminoalkyltrialkoxysilane (in isopropanol).

[0041] Preferably, in step 2, the mass ratio of the dried kaolinite to the coupling agent containing terminal amino groups is 10:1.

[0042] Preferably, in step 3, the molar ratio of the intermediate compound to the kaolinite modified by the amino-containing coupling agent is 1-1.05.

[0043] Preferably, in step 4, the mass ratio of the dried modified kaolinite to the waste resin is 1-5:97.

[0044] The following is further described in conjunction with specific embodiments.

[0045] Example 1

[0046] (1) 0.2 mol of cyanuric chloride (CC) and an excess of vanillin (BM) were introduced into a three-necked flask containing 90 mL of dichloromethane and reacted at 80° C. for 6 h to prepare an intermediate compound (CC-BM), the infrared spectrum of which is shown in FIG. Figure 1 As shown;

[0047] Depend on Figure 1 As shown, the hydroxyl vibration peak (3177 cm -1 ) did not appear in CC-BM, indicating that the hydroxyl groups in BM had reacted completely. At the same time, the C-Cl vibration peak (834cm -1 ) also did not appear in CC-BM, proving that the C-Cl in CC and the hydroxyl group of BM have reacted completely, and the product has a peak at 1694 cm -1 The aldehyde group of BM was found at 1665 cm -1 1694cm transferred to CC-BM -1 ). At the same time, the vibration peaks of CC and BM benzene ring skeletons were also found, proving that the CC-BM synthesis was successful.

[0048] (2) γ-aminopropyltriethoxysilane (KH-NH2) with a mass of one tenth of Kaol is added to deionized water. After sufficient hydrolysis, an appropriate amount of dried kaolinite (Kaol) is added to the above solution. The mixture is stirred at 90°C for 5 h to prepare KH-NH2-modified kaolinite KH-NH2-Kaol, whose infrared spectrum is shown in FIG. Figure 2 As shown;

[0049] Depend on Figure 2 As shown in the figure, the relative intensities of the two types of hydroxyl groups of Kaol changed significantly after KH-NH2 modification, among which the inner surface hydroxyl group at 3694 cm -1 (Easily reactive) relative to the internal hydroxyl group of Kaol (3620cm -1 , difficult to react) decreased seriously, indicating that the inner surface hydroxyl of Kaol and KH-NH2 changed, and at 2927cm -1 The vibration peak of CH appeared at , indicating that KH-NH2 has been grafted onto the kaolinite surface.

[0050] (3) CC-BM and KH-NH2-Kaol with a molar ratio of 1.01 were added to a three-necked bottle containing deionized water and reacted at 90°C under stirring for 12 h to prepare modified kaolinite CC-BM@KH-NH2-Kaol, whose infrared spectrum is shown in Figure 3 As shown;

[0051] Depend on Figure 3As shown in the figure, the characteristic peaks of the intermediate products can be clearly found in CC-BM@KH-NH2-Kaol. -1 The aldehyde group nearby has a serious decrease, and the -1 The characteristic peak of the newly generated Schiff base (C=N) was found at , indicating that the amino group of KH-NH2 reacted with the aldehyde group of CC-BM to finally generate CC-BM@KH-NH2-Kaol.

[0052] (4) Then the dried CC-BM@KH-NH2-Kaol and waste resin (such as waste packaging scraps, polypropylene) are melt-blended and pelletized by an extruder (processing temperature of 180, 190, 200°C, speed of 35r / min) at a material ratio of 3:97 to prepare CC-BM@KH-NH2-Kaol waste resin reinforced flame retardant composite materials;

[0053] (5) Then place the diced composite material on a 10×10×3mm 3 The mold was placed between the upper and lower hot pressing sheets of the hot pressing machine, wherein the hot pressing temperature was 200°C, the hot pressing was performed for 4 minutes, and then the air was released, and this was repeated 4 times, and then the sample was taken out and cold pressed to obtain a flame retardant test sample. The relevant performance test data (pHRR) are shown in Table 1;

[0054] (6) Finally, the crushed composite material is melt-molded into the specimens required for mechanical property testing by an injection molding machine. The relevant parameters are as follows: barrel zone 1 220°C, barrel zone 2 220°C, barrel zone 3 220°C, nozzle temperature 220°C, injection pressure 30 MPa, injection time 3 s, holding time 20 s. The relevant performance test data are shown in Table 1.

[0055] Example 2

[0056] (1) 0.2 mol of cyanuric chloride (CC) and an excess of bio-based material (compounds containing both hydroxyl and aldehyde functional groups, BM) were introduced into a three-necked flask containing 90 mL of dichloromethane and reacted at 80° C. under stirring for 6 h to prepare an intermediate compound (CC-BM), whose infrared spectrum is shown in FIG. Figure 1 As shown;

[0057] (2) Take one tenth of the mass of Kaol and add the amino-containing coupling agent (KH-NH2) to deionized water. After sufficient hydrolysis, add an appropriate amount of dried kaolinite (Kaol) to the above solution and react at 90°C under stirring for 5 hours to prepare KH-NH2-modified kaolinite KH-NH2-Kaol, whose infrared spectrum is shown in the following figure: Figure 2 As shown;

[0058] (3) CC-BM and KH-NH2-Kaol with a molar ratio of 1.01 were added to a three-necked bottle containing deionized water and reacted at 90°C under stirring for 12 h to prepare modified kaolinite CC-BM@KH-NH2-Kaol, whose infrared spectrum is shown in Figure 3 As shown;

[0059] (4) Then the dried CC-BM@KH-NH2-Kaol and waste resin (such as waste packaging scraps, polypropylene) are melt-blended and pelletized by an extruder (processing temperature of 180, 190, 200°C, speed of 35r / min) at a material ratio of 1:99 to prepare CC-BM@KH-NH2-Kaol waste resin reinforced flame retardant composite materials;

[0060] (5) Then place the diced composite material on a 10×10×3mm 3 The mold was placed between the upper and lower hot pressing sheets of the hot pressing machine, wherein the hot pressing temperature was 200°C, the hot pressing was performed for 4 minutes, and then the air was released, and this was repeated 4 times, and then the sample was taken out and cold pressed to obtain a flame retardant test sample. The relevant performance test data (pHRR) are shown in Table 1;

[0061] (6) Finally, the crushed composite material is melt-molded into the specimens required for mechanical property testing by an injection molding machine. The relevant parameters are as follows: barrel zone 1 220°C, barrel zone 2 220°C, barrel zone 3 220°C, nozzle temperature 220°C, injection pressure 30 MPa, injection time 3 s, holding time 20 s. The relevant performance test data are shown in Table 1.

[0062] Example 3

[0063] (1) 0.2 mol of cyanuric chloride (CC) and an excess of bio-based material (compounds containing both hydroxyl and aldehyde functional groups, BM) were introduced into a three-necked flask containing 90 mL of dichloromethane and reacted at 80° C. under stirring for 6 h to prepare an intermediate compound (CC-BM), whose infrared spectrum is shown in FIG. Figure 1 As shown;

[0064] (2) Take one tenth of the mass of Kaol and add the amino-containing coupling agent (KH-NH2) to deionized water. After sufficient hydrolysis, add an appropriate amount of dried kaolinite (Kaol) to the above solution and react at 90°C under stirring for 5 hours to prepare KH-NH2-modified kaolinite KH-NH2-Kaol, whose infrared spectrum is shown in the following figure: Figure 2 As shown;

[0065] (3) CC-BM and KH-NH2-Kaol with a molar ratio of 1.01 were added to a three-necked bottle containing deionized water and reacted at 90°C under stirring for 12 h to prepare modified kaolinite CC-BM@KH-NH2-Kaol, whose infrared spectrum is shown in Figure 3 As shown;

[0066] (4) Then the dried CC-BM@KH-NH2-Kaol and waste resin (such as waste packaging scraps, polypropylene) are melt-blended and pelletized by an extruder (processing temperature of 180, 190, 200°C, speed of 35r / min) at a material ratio of 5:95 to prepare CC-BM@KH-NH2-Kaol waste resin reinforced flame retardant composite materials;

[0067] (5) Then place the diced composite material on a 10×10×3mm 3 The mold was placed between the upper and lower hot pressing sheets of the hot pressing machine, wherein the hot pressing temperature was 200°C, the hot pressing was performed for 4 minutes, and then the air was released, and this was repeated 4 times, and then the sample was taken out and cold pressed to obtain a flame retardant test sample. The relevant performance test data (pHRR) are shown in Table 1;

[0068] (6) Finally, the crushed composite material is melt-molded into the specimens required for mechanical property testing by an injection molding machine. The relevant parameters are as follows: barrel zone 1 220°C, barrel zone 2 220°C, barrel zone 3 220°C, nozzle temperature 220°C, injection pressure 30 MPa, injection time 3 s, holding time 20 s. The relevant performance test data are shown in Table 1.

[0069] Table 1: Performance test data of modified kaolinite reinforced flame retardant ABS composites

[0070]

[0071] As can be seen from Table 1, CC-BM@KH-NH2-Kaol can effectively improve the flame retardant and mechanical properties of waste resin, and therefore, can meet the higher-end and broader applications of waste resin composites, such as cement bag materials.

[0072] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a modified kaolinite reinforced flame retardant waste resin composite material, characterized in that: The following steps are involved: Step 1: adding cyanuric chloride and a bio-based material to a solvent, stirring and reacting at a high temperature to prepare an intermediate compound; wherein the bio-based material is vanillin; the solvent is dichloromethane; in step 1, the temperature of the stirring reaction at a high temperature is 80° C., and the time is 6 hours; Step 2: add a coupling agent containing an amino group to water, and after sufficient hydrolysis, add dried kaolinite thereto, stir and react at high temperature to prepare kaolinite modified by an amino group-containing coupling agent; in step 2, the mass ratio of the dried kaolinite to the coupling agent containing an amino group is 10:1; in step 2, the coupling agent containing an amino group is γ-aminopropyltriethoxysilane; in step 2, the temperature of the stirring reaction at high temperature is 90°C, and the time is 5h; Step 3: adding the intermediate compound and the kaolinite modified by the coupling agent containing an amino group into a container of deionized water, and reacting them under stirring at 90° C. for 12 hours to prepare modified kaolinite; wherein the molar ratio of the intermediate compound to the kaolinite modified by the coupling agent containing an amino group is 1.01; Step 4: melt-blending the dried modified kaolinite and waste resin to prepare a modified kaolinite reinforced flame-retardant waste resin composite material; in step 4, the mass ratio of the dried modified kaolinite and waste resin is 5:95, and the waste resin is polypropylene.

2. A modified kaolinite reinforced flame retardant waste resin composite material prepared by the preparation method as claimed in claim 1.

Citation Information

Patent Citations

  • Intumescent flame-retardant polypropylene and preparation method thereof

    CN111040293A